Assessment of Coagulation by Thromboelastography During Ongoing Postpartum Hemorrhage: A Retrospective Cohort Analysis. Issue 3 (September 2020) - Rigouzzo, A.; Louvet, N.; Favier, R.; Ore, M.V.; Piana, F.; Girault, L.; Farrugia, M.; Sabourdin, N.; Constant, I.
Abstract : ( Anesth Analg . 2020;130:416–425) Early detection is crucial in the management of postpartum hemorrhage (PPH), a leading global cause of maternal mortality. A fibrinogen concentration ⩽2 g/L at the onset of PPH is a strong predictive factor, but measurement of fibrinogen level takes too long to obtain for decision-making. Thromboelastography (TEG) is a point of care coagulation monitor that may be able to guide management and improve outcomes in PPH patients. This study aimed to evaluate TEG parameters for accuracy in the diagnosis of coagulopathy during PPH and accuracy in the prediction of severe hemorrhage >2500 mL.